2015
DOI: 10.1073/pnas.1424355112
|View full text |Cite
|
Sign up to set email alerts
|

COX/mPGES-1/PGE 2 pathway depicts an inflammatory-dependent high-risk neuroblastoma subset

Abstract: The majority of solid tumors are presented with an inflammatory microenvironment. Proinflammatory lipid mediators including prostaglandin E 2 (PGE 2 ) contribute to the establishment of inflammation and have been linked to tumor growth and aggressiveness. Here we show that high-risk neuroblastoma with deletion of chromosome 11q represents an inflammatory subset of neuroblastomas. Analysis of enzymes involved in the production of proinflammatory lipid mediators showed that 11q-deleted neuroblastoma tumors expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 46 publications
5
90
0
2
Order By: Relevance
“…Expression of genes representing TAMs (CD33/CD16/IL-10/FCGR3) in addition to IL-6 receptor (IL-6R) contributed to 25% of the accuracy of a novel 14-gene tumor classification score [13]. Infiltration with Th2-driven macrophages expressing CD163 and CD206 was also recently observed in a subset of high-risk neuroblastoma tumors with deletion of chromosome 11q and high levels of prostaglandin-synthase and elevated levels of PGE2 [14]. …”
Section: Introduction: Neuroblastoma a Cancer Not Solely Driven By Gmentioning
confidence: 99%
“…Expression of genes representing TAMs (CD33/CD16/IL-10/FCGR3) in addition to IL-6 receptor (IL-6R) contributed to 25% of the accuracy of a novel 14-gene tumor classification score [13]. Infiltration with Th2-driven macrophages expressing CD163 and CD206 was also recently observed in a subset of high-risk neuroblastoma tumors with deletion of chromosome 11q and high levels of prostaglandin-synthase and elevated levels of PGE2 [14]. …”
Section: Introduction: Neuroblastoma a Cancer Not Solely Driven By Gmentioning
confidence: 99%
“…An increased expression of mPGES-1 in the tissues of patients of brain cancer has also been reported from another group in a subset of human glioblastoma multiforme (GBM) tumors, the most common form of adult brain cancer, astrocytoma and high-risk neuroblastoma. [45][46][47] An activated COX/mPGES-1/PGE 2 pathway has been identified in 11q-deleted neuroblastoma with high expression of mPGES-1, and elevated levels of PGE 2 as compared with low-risk tumors. Analysis of expression cohorts revealed a worse outcome for high-risk patients (INSS stage 4) with high mPGES-1 expression.…”
Section: Role Of Mpges-1 In Brain Cancermentioning
confidence: 99%
“…Analysis of expression cohorts revealed a worse outcome for high-risk patients (INSS stage 4) with high mPGES-1 expression. 47) In accordance with the anti-apoptotic properties of COX-2, which is known to play an important role in tumor development, in an in vitro study using the human astroglioma cell line U-87MG, PGE 2 produced by overexpression of mPGES-1 promoted glioma proliferation through activation of type 2 protein kinase A. 46) COX inhibition in an in vivo model of 11q-deleted neuroblastoma also demonstrated that PGE 2 produced by mPGES-1 resulted in promotion of tumor growth.…”
Section: Role Of Mpges-1 In Brain Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of mPGES-1 have been found in various cancers, including non-small-cell lung cancer, colon cancer, and prostate cancer [Larsson et al, 2015]. Animal studies have shown that chemical inhibition or the elimination of COX-2 activity results in a decreased or slower tumor formation [Jänne and Mayer, 2000;Ettarh et al, 2010].…”
Section: Introductionmentioning
confidence: 99%